Effects of Sophorae Radix on Human Gastric and Colorectal Adenocarcinoma Cells: Sophorae Radix and Cancer Cells - Kim, Min-Chul (J Pharmacopuncture, 2012)
The purpose of this study was to investigate the anti-cancer effects of Sophorae Radix (SR) and doxorubicin (DOX) in human gastric and colorectal adenocarcinoma cells. We used the human gastric and colorectal adenocarcinoma cell lines (MKN-45 and WIDR cells, respectively). We examined cell death by using the MTT(3-[4, 5-dimethylthiazol-2-yl]-2, 5- diphenyltetrazolium bromide) assay and the caspase 3 assay with SR. To examine the inhibitory effects of SR, we performed a cell cycle (sub G1) analysis for the MKN-45 and WIDR cells after three days with SR. The reversibility of SR was examined for one-day to five-day treatments with SR. SR inhibited the growth of MKN-45 and WIDR cells in a dosedependent manner. Also, we showed that SR induced apoptosis in MKN-45 and WIDR cells by using the MTT assay, the caspase 3 assay and the sub-G1 analysis. SR combined with DOX markedly inhibited the growth of MKN-45 and WIDR cells compared to SR or DOX alone. After 3 days of treating MKN-45 and WIDR cells with SR, the fraction of cells in the sub-G1 phase was much higher than that of the control group. Our findings provide insights into unraveling the effects of SR on human gastric and colorectal adenocarcinoma cells and into developing therapeutic agents for use against gastric and colorectal adenocarcinomas.